2004
DOI: 10.1159/000084159
|View full text |Cite
|
Sign up to set email alerts
|

Language-Specific Articulatory Settings: Evidence from Inter-Utterance Rest Position

Abstract: The possible existence of language-specific articulatory settings (underlying or default articulator positions) has long been discussed, but these have proven elusive to direct measurement. This paper presents two experiments using X-ray data of 5 English and 5 French subjects linking articulatory setting to speech rest position, which is measurable without segmental interference. Results of the first experiment show that speech rest position is significantly different across languages at 5 measurement locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 27 publications
4
56
0
4
Order By: Relevance
“…In their sample of eight bilingual speakers, four were rated as being native in both of their languages, while for the other four this was not the case. The speakers in the first group generally exhibited articulatory setting differences between their two native languages, which were in line with the differences between English native speakers and French native speakers: lower tongue tip height (reported by Gick et al, 2004, andWilson, 2013) and more lower lip protrusion for French speakers compared to English speakers (reported by Wilson, 2013). The speakers in the second group did not exhibit a similar pattern.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…In their sample of eight bilingual speakers, four were rated as being native in both of their languages, while for the other four this was not the case. The speakers in the first group generally exhibited articulatory setting differences between their two native languages, which were in line with the differences between English native speakers and French native speakers: lower tongue tip height (reported by Gick et al, 2004, andWilson, 2013) and more lower lip protrusion for French speakers compared to English speakers (reported by Wilson, 2013). The speakers in the second group did not exhibit a similar pattern.…”
supporting
confidence: 60%
“…For this purpose, techniques such as x-ray, ultrasound, electromagnetic articulography (EMA), and real-time magnetic resonance imaging can be used (Mennen et al, 2010;Ramanarayanan et al, 2013). Gick et al (2004) used x-ray data (with a sample of ten speakers) to show that there were language-specific articulatory settings for English vs French speakers. They found that compared to English, French was characterized by a greater pharynx width, a lower tongue body, a lower tongue tip, a less protruded upper lip, and a more protruded lower lip (although see Wilson, 2013, for a different pattern), but that velum and jaw positions did not differ significantly between the two groups.…”
mentioning
confidence: 99%
“…A real-time MRI study of spontaneous speech by Ramanarayanan et al [95,96] has found that the position of the articulators during grammatical pauses (defined as pauses that occur between syntactic constituents and excluding hesitation and word search pauses, in other words, pauses that can be assumed to be prosodic boundaries) show least variability, followed by ready-to-speak postures (i.e. postures of articulators that speakers adopt immediately before starting to speak, see also [97,98], followed by rest positions). As pointed out by Ramanarayanan et al [95], lower variability can be understood as more control over the vocal tract, indicating that pauses at prosodic boundaries are planned, whereas the ready-to-speak pauses are less planned.…”
Section: Cognitive Functions Of Prosodic Boundaries (A) Pauses and Spmentioning
confidence: 99%
“…10 Mucho más recientemente, Gick et al (2005), Wilson (2006) y Schaeffler, Scobbie y Mennen (2008 han estudiado las 'posturas de trabajo' de varias lenguas y han conseguido establecer mediante técnicas objetivas (sistemas de captura de movimientos en 3D por ultrasonidos, cinerradiografía, etc.) que las −así llamadas por todos ellos− inter-speech postures divergen, en efecto y significativamente, al menos entre la variedad canadiense del inglés y del francés.…”
Section: Discusión De Los Resultadosunclassified